A composite latex liquid, preparation method thereof and latex product

By adding modified inorganic powder to natural latex, the problem of poor mechanical properties of natural latex gloves is solved, and the mechanical properties of latex products are improved and the safety of use is enhanced.

CN119161595BActive Publication Date: 2025-03-18PEKING UNIVERSITY THIRD HOSPITAL (THE THIRD CLINICAL MEDICAL SCHOOL OF PEKING UNIVERSITY)
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411649278.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-18
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The mechanical properties of existing natural latex gloves are poor and it is difficult to provide sufficient safety for use.

Method used

Modified inorganic powder is added to natural latex, and the inorganic powder is treated by activation and hydrophobic modification, so that it is mixed with natural latex more evenly, thereby improving the mechanical properties of latex products.

Benefits of technology

It effectively improves the mechanical properties of latex products, enhances the safety of users, while maintaining the simplicity and low cost of the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present disclosure relates to the technical field of latex materials, and in particular to a composite latex liquid, a preparation method thereof, and a latex product. The present disclosure adopts a silane coupling agent to hydrophobically modify an inorganic powder, thereby enhancing its dispersibility in natural latex, making it more uniform during mixing with natural latex, and avoiding agglomeration, thereby effectively enhancing the mechanical properties of latex products prepared using the composite latex liquid of the present disclosure, and improving the safety of use; at the same time, the preparation process of the composite latex liquid of the present disclosure is simple, the cost is low, and it has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of latex materials, and in particular to a composite latex liquid, a preparation method thereof, and a latex product. Background Art

[0002] Medical surgical gloves can protect the safety of the operator well because of their barrier protection. They can protect the operator's hand skin from damage and infection, and protect the body of the operator from bacteria and stolen goods carried by the operator. However, the commonly used natural latex gloves have poor mechanical properties and will inevitably be damaged by the touch of a scalpel or surgical thread. Therefore, in order to improve the safety of natural latex gloves, it is imperative to prepare high-performance natural latex products.

[0003] CN102675698A discloses a mixed latex liquid, comprising natural latex, chloroprene latex, deionized water, sulfur, ZDC accelerator, antioxidant D, zinc oxide, potassium hydroxide, casein and lanolin with a weight percentage concentration of 60%, and the content of each component is limited. Since the mixed latex liquid is obtained by adding additives such as chloroprene latex to natural latex, the mixed latex liquid is used to make latex gloves, which improves the anti-aging performance, flexibility resistance, chemical resistance and elasticity of the latex gloves; it is softer than pure natural latex and has stronger anti-grease and other properties. However, the latex products prepared by the mixed latex liquid still have poor mechanical properties and cannot provide sufficient safety in use.

[0004] Therefore, how to provide a method for improving the mechanical properties of latex materials has become a problem that needs to be solved urgently. Summary of the invention

[0005] In order to solve the above technical problems, the present disclosure provides a composite latex liquid, a preparation method thereof and a latex product. The composite latex liquid is prepared by adding modified inorganic powder to natural latex. The latex product prepared using the composite latex liquid can effectively improve its mechanical properties, thereby enhancing the safety of use by users.

[0006] In a first aspect, the present disclosure provides a method for preparing a composite latex, the preparation method comprising the following steps:

[0007] (1) Activating the inorganic powder with alkali solution to obtain activated inorganic powder;

[0008] (2) mixing the activated inorganic powder obtained in step (1) with an acid solution to obtain a dispersion;

[0009] (3) mixing the dispersion obtained in step (2) with a hydrophobic silane coupling agent and reacting the mixture so that the hydrophobic silane coupling agent is grafted onto the surface of the activated inorganic powder to obtain a modified inorganic powder;

[0010] (4) Mixing the modified inorganic powder obtained in step (3) with a latex base liquid to obtain a composite latex liquid.

[0011] The present invention firstly activates the inorganic powder with an alkaline solution to generate silanol functional groups on its surface; then adds a hydrophobic silane coupling agent in an acid environment to allow the hydrophobic silane coupling agent to act with the silanol functional groups on the surface of the inorganic powder in the form of a covalent bond, thereby being grafted onto the surface of the inorganic powder, thereby completing the hydrophobic modification of the inorganic powder and making it more evenly dispersed in the process of mixing with a latex base liquid in the later stage, thereby avoiding local agglomeration, thereby improving the mechanical properties of the resulting latex product and ensuring the safety of the user.

[0012] The following are preferred technical solutions of the present disclosure, but are not intended to be limitations of the technical solutions provided by the present disclosure. Through the following technical solutions, the technical objectives and beneficial effects of the present disclosure can be better achieved and realized.

[0013] As a preferred technical solution of the present disclosure, the alkaline solution in step (1) includes sodium hydroxide solution.

[0014] As a preferred technical solution of the present disclosure, the concentration of the alkali solution in step (1) is 0.5-1.5 mol / L, such as 0.5 mol / L, 1 mol / L or 1.5 mol / L, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0015] As a preferred technical solution of the present disclosure, the inorganic powder in step (1) includes one or more of silicon dioxide, sepiolite or montmorillonite, preferably a combination of silicon dioxide and sepiolite.

[0016] As a preferred technical solution of the present disclosure, the average particle size of the inorganic powder in step (1) is 100-500 nm, for example, 100 nm, 150 nm, 200 nm, 300 nm, 400 nm or 500 nm, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0017] As a preferred technical solution of the present disclosure, the volume mass ratio of the alkali solution to the inorganic powder in step (1) is 25mL:(0.1-1)g, for example, 25mL:0.1g, 25mL:0.2g, 25mL:0.5g, 25mL:0.8g or 25mL:1g, etc., but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0018] As a preferred technical solution of the present disclosure, stirring and ultrasonic treatment are performed in sequence during the activation treatment in step (1), and the time of the ultrasonic treatment is not less than 30 minutes, for example, 30 minutes, 35 minutes, 40 minutes, 45 minutes or 50 minutes, etc., but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0019] As a preferred technical solution of the present disclosure, the inorganic powder in step (1) includes silicon dioxide and sepiolite.

[0020] The mass ratio of the silicon dioxide to the sepiolite is 1:(0.5-3), such as 1:0.5, 1:1, 1:2 or 1:3, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0021] The present invention uses two inorganic powders in combination and limits the addition ratio of the two. Compared with adding a single modified inorganic powder, the two powders work synergistically to greatly improve the tensile properties of the prepared latex product.

[0022] As a preferred technical solution of the present disclosure, the acid solution in step (2) includes hydrochloric acid.

[0023] As a preferred technical solution of the present disclosure, the pH of the dispersion in step (2) is 3-4, such as 3, 3.2, 3.4, 3.6, 3.8 or 4, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0024] As a preferred technical solution of the present disclosure, the hydrophobic silane coupling agent in step (3) includes a silane coupling agent having a non-hydrolyzable hydrophobic carbon chain, generally a long-chain alkyl silane coupling agent having a carbon number of not less than 3.

[0025] As a preferred technical solution of the present disclosure, the mass ratio of the activated inorganic powder in the dispersion of step (3) to the hydrophobic silane coupling agent is (1-5):1, such as 1:1, 2:1, 3:1, 4:1 or 5:1, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0026] An appropriate amount of hydrophobic silane coupling agent can effectively modify inorganic powders, but adding too much will increase costs and waste resources.

[0027] As a preferred technical solution of the present disclosure, the reaction time of step (3) is 4-6 h, for example, 4 h, 4.5 h, 5 h, 5.5 h or 6 h, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0028] As a preferred technical solution of the present disclosure, after the reaction in step (3) is completed, the obtained solid product is washed and dried to obtain a modified inorganic powder.

[0029] Preferably, the solid product obtained after the reaction in step (3) is dried at 100-120°C, for example, 100°C, 105°C, 110°C, 115°C or 120°C, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0030] As a preferred technical solution of the present disclosure, the silane coupling agent having a non-hydrolyzable hydrophobic carbon chain includes hexadecyltrimethoxysilane (denoted as HDTMS) and / or isocyanatepropyltriethoxysilane (denoted as ICPES).

[0031] As a preferred technical solution of the present disclosure, the latex base liquid in step (4) includes natural latex;

[0032] Or, the latex base liquid in step (4) comprises natural latex, sulfur dispersion, accelerator and zinc oxide dispersion;

[0033] The accelerator includes zinc dimethyldithiocarbamate and / or 2-mercaptobenzothiazole;

[0034] The mass ratio of the natural latex, the sulfur dispersion, the accelerator and the zinc oxide dispersion is 100:1:1:0.5.

[0035] Adding the modified inorganic powder disclosed in the present invention will not only have no adverse effects on the vulcanization process of latex products, but also increase the smoothness of latex products while improving their mechanical properties and reducing their surface viscosity and roughness.

[0036] As a preferred technical solution of the present disclosure, the added mass of the modified inorganic powder in step (4) is 0.1-2% of the mass of the latex base liquid, such as 0.1%, 0.5%, 1%, 1.5% or 2%, etc., but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0037] In the present disclosure, a reasonable amount of modified inorganic powder added is helpful to improve the mechanical properties of latex products. If it is added too much, it will lead to uneven dispersion of inorganic powder and reduced mechanical properties.

[0038] In a second aspect, the present disclosure provides a composite latex liquid prepared by the preparation method described in the first aspect.

[0039] In a third aspect, the present disclosure provides a latex product, wherein part or all of the material of the latex product is obtained by curing the composite latex liquid as described in the second aspect;

[0040] The curing temperature is 60-120° C., such as 60° C., 80° C., 100° C. or 120° C., but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0041] As a preferred technical solution of the present disclosure, the latex product includes medical non-surgical gloves.

[0042] Compared with the prior art, the technical solution provided by the embodiments of the present disclosure has the following advantages:

[0043] The present invention adopts a silane coupling agent to perform hydrophobic modification on inorganic powder, thereby enhancing its dispersibility in natural latex, making it more uniform during mixing with natural latex and avoiding agglomeration, thereby effectively enhancing the mechanical properties of latex products prepared using the composite latex liquid of the present invention and improving safety of use; at the same time, the preparation process of the composite latex liquid of the present invention is simple, the cost is low, and it has good application prospects. DETAILED DESCRIPTION

[0044] In order to more clearly understand the above-mentioned objectives, features and advantages of the present disclosure, the scheme of the present disclosure will be further described below. It should be noted that the embodiments of the present disclosure and the features in the embodiments can be combined with each other without conflict.

[0045] In the following description, many specific details are set forth to facilitate a full understanding of the present disclosure, but the present disclosure may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present disclosure, rather than all of the embodiments.

[0046] Example 1

[0047] This embodiment provides a method for preparing a composite latex solution, the preparation method comprising the following steps:

[0048] (1) 0.5 g of silica with an average particle size of 100 nm was mixed with 25 mL of 1 mol / L sodium hydroxide solution, stirred for 15 min, then ultrasonically treated for 35 min, and then centrifuged and washed with ethanol to obtain activated silica;

[0049] (2) mixing the activated silicon dioxide obtained in step (1) with hydrochloric acid to obtain a dispersion having a pH of 3;

[0050] (3) 0.5 g of hexadecyltrimethoxysilane (i.e., HDTMS) was mixed with the dispersion obtained in step (2) and reacted for 4 h to allow the hexadecyltrimethoxysilane to be grafted onto the surface of the activated silica, followed by centrifugation and ethanol washing, and then drying at 120° C. for 2 h to obtain modified silica;

[0051] (4) The modified silica obtained in step (3) is mixed evenly with 50 g of natural latex to obtain a composite latex solution.

[0052] Example 2

[0053] This embodiment provides a method for preparing a composite latex liquid. The preparation method is similar to the preparation method in Example 1, except that: the mass of the silicon dioxide used in step (1) is 1 g;

[0054] At the same time, in order to ensure that the added mass of modified silica in step (4) is still 1% of the mass of natural latex, the added amount of natural latex is changed to 100 g.

[0055] Example 3

[0056] This embodiment provides a method for preparing a composite latex liquid. The preparation method is similar to the preparation method in Example 1, with the only difference being that 0.1 g of hexadecyltrimethoxysilane (i.e., HDTMS) is used in step (3).

[0057] Example 4

[0058] This embodiment provides a method for preparing a composite latex liquid. The preparation method is similar to the preparation method in Example 3, except that the silicon dioxide with an average particle size of 100 nm in step (1) is replaced by sepiolite with an average particle size of 500 nm.

[0059] Example 5

[0060] This embodiment provides a method for preparing a composite latex solution, the preparation method comprising the following steps:

[0061] (1) 0.5 g of silicon dioxide with an average particle size of 100 nm, 0.5 g of sepiolite with an average particle size of 500 nm and 25 mL of 0.5 mol / L sodium hydroxide solution were mixed, stirred for 10 min, then ultrasonically treated for 30 min, and then centrifuged and washed with ethanol to obtain activated silicon dioxide and activated sepiolite;

[0062] (2) mixing the activated silicon dioxide and activated sepiolite obtained in step (1) with hydrochloric acid to obtain a dispersion having a pH of 4;

[0063] (3) 0.2 g of hexadecyltrimethoxysilane (i.e., HDTMS) was mixed with the dispersion obtained in step (2) and reacted for 4 h to allow the hexadecyltrimethoxysilane to be grafted onto the surfaces of the activated silica and the activated sepiolite, followed by centrifugation and ethanol washing in sequence, and then drying at 110° C. for 2 h to obtain modified silica and modified sepiolite;

[0064] (4) The modified silica and modified sepiolite obtained in step (3) are uniformly mixed with 100 g of natural latex to obtain a composite latex solution.

[0065] Example 6

[0066] This embodiment provides a method for preparing a composite latex liquid. The preparation method is similar to the preparation method of Example 5, with the only difference being that in step (1), the amount of silicon dioxide used is 0.25 g, and the amount of sepiolite used is 0.75 g.

[0067] Example 7

[0068] This embodiment provides a method for preparing a composite latex liquid. The preparation method is similar to the preparation method of Example 4, except that the hexadecyltrimethoxysilane (HDTMS) used in step (3) is replaced by isocyanatepropyltriethoxysilane (ICPES).

[0069] Comparative Example 1

[0070] This comparative example provides a natural latex, which is exactly the same as the natural latex used in step (4) of Example 1 and has a mass of 50 g.

[0071] Comparative Example 2

[0072] This comparative example provides a method for preparing a composite latex liquid. The preparation method refers to the preparation method in Example 1, with the only difference being that steps (1) to (3) are not performed, i.e., the silicon dioxide is not modified, and in step (4), only 0.5 g of silicon dioxide having an average particle size of 100 nm is mixed evenly with 50 g of natural latex to obtain a composite latex liquid.

[0073] Comparative Example 3

[0074] This comparative example provides a method for preparing a composite latex liquid. The preparation method refers to the preparation method in Example 4, with the only difference being that steps (1) to (3) are not performed, i.e., the sepiolite is not modified, and in step (4), only 0.5 g of sepiolite with an average particle size of 500 nm is mixed evenly with 50 g of natural latex to obtain a composite latex liquid.

[0075] Comparative Example 4

[0076] This comparative example provides a method for preparing a composite latex liquid. The preparation method refers to the preparation method in Example 4, with the only difference being that the hexadecyltrimethoxysilane (i.e., HDTMS) used in step (3) is replaced by 3-(2,3-epoxypropoxy)propyltrimethoxysilane (i.e., KH560).

[0077] Tensile properties test:

[0078] Take 2.5mL of the latex liquid to be tested, place it in a silicone mold, spread it evenly, control the thickness to 0.4mm±0.1mm, cure it at 90℃, cut it into 5cm×1cm strip sample films, stretch it at a speed of 500mm / min, and record the force when it breaks; take two samples (the obtained latex films) for testing respectively, and take the average value of the results.

[0079] According to the above corresponding test methods, the test results of the latex samples obtained in Examples 1-7 and Comparative Examples 1-4 are shown in Table 1.

[0080] Table 1

[0081]

[0082]

[0083] It can be seen from Table 1 that, compared with the sample of Comparative Example 1, the tensile properties of the samples prepared using the composite latex solution of Examples 1-7 are improved by more than 64%.

[0084] Furthermore, by comparing Example 5 with Example 3 and Example 4, two inorganic powders are compounded and their addition ratio is limited. Compared with adding a single modified inorganic powder, the two powders synergistically exert a stronger effect, thereby greatly improving the tensile properties of the latex sample.

[0085] Compared with the comparative example 2 in which unmodified silica was added, the silica modified by the disclosed method was added in the example 1, and the tensile properties of the sample latex film were improved by more than 8%.

[0086] Compared with the unmodified sepiolite added in Comparative Example 3, the sepiolite modified by the disclosed method was added in Example 4, and the tensile properties of the sample latex film were improved by more than 59%.

[0087] By comparing Comparative Example 4 with Example 4 and Comparative Example 3, it can be seen that since KH560 used in Comparative Example 4 has a hydrophilic epoxy group, after the inorganic powder is modified with it, the powder surface still has a certain hydrophilicity, and the water phase in the emulsion has poor compatibility with the polymer. Therefore, after the inorganic powder is modified with it, the mechanical properties of the latex product are reduced, which has a counter-effect.

[0088] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0089] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a composite latex, characterized in that: The preparation method comprises the following steps: (1) Activating the inorganic powder with alkali solution to obtain activated inorganic powder; The average particle size of the inorganic powder is 100-500nm; The inorganic powder includes silicon dioxide and sepiolite; The mass ratio of the silicon dioxide to the sepiolite is 1:1; (2) mixing the activated inorganic powder obtained in step (1) with an acid solution to obtain a dispersion; (3) mixing the dispersion obtained in step (2) with a hydrophobic silane coupling agent and reacting the mixture so that the hydrophobic silane coupling agent is grafted onto the surface of the activated inorganic powder to obtain a modified inorganic powder; The mass ratio of the activated inorganic powder in the dispersion to the hydrophobic silane coupling agent is (1-5):1; The hydrophobic silane coupling agent includes a silane coupling agent having a non-hydrolyzable hydrophobic carbon chain; The silane coupling agent having a non-hydrolyzable hydrophobic carbon chain includes hexadecyltrimethoxysilane and / or isocyanatepropyltriethoxysilane; (4) Mixing the modified inorganic powder obtained in step (3) with a latex base liquid to obtain a composite latex liquid.

2. The preparation method according to claim 1, characterized in that: The alkali solution in step (1) includes sodium hydroxide solution; And / or, the concentration of the alkali solution in step (1) is 0.5-1.5 mol / L; And / or, the volume mass ratio of the alkali solution to the inorganic powder in step (1) is 25 mL: (0.1-1) g; And / or, during the activation treatment in step (1), stirring and ultrasonic treatment are performed in sequence, and the ultrasonic treatment time is not less than 30 minutes.

3. The preparation method according to claim 1, characterized in that: The acid solution in step (2) includes hydrochloric acid; And / or, the pH of the dispersion in step (2) is 3-4.

4. The preparation method according to claim 1, characterized in that: The reaction time of step (3) is 4-6 hours; And / or, the preparation method further comprises, after the reaction in step (3) is completed, washing and drying the obtained solid product to obtain a modified inorganic powder.

5. The preparation method according to claim 1, characterized in that: The latex base liquid in step (4) includes natural latex.

6. The preparation method according to claim 5, characterized in that: The latex base liquid in step (4) comprises natural latex, sulfur dispersion, accelerator and zinc oxide dispersion; The accelerator includes zinc dimethyldithiocarbamate and / or 2-mercaptobenzothiazole; The mass ratio of the natural latex, the sulfur dispersion, the accelerator and the zinc oxide dispersion is 100:1:1:0.

5.

7. The preparation method according to claim 1, characterized in that: The added mass of the modified inorganic powder in step (4) is 0.1-2% of the mass of the latex base liquid.

8. A composite latex solution, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 7.

9. A latex product, characterized in that: Part or all of the material of the latex product is obtained by curing the composite latex liquid as claimed in claim 8; The curing temperature is 60-120°C.

Citation Information

Patent Citations

  • Mixed latex solution

    CN102675698A

  • Wear-resistant heat-insulating glove and preparation method thereof

    CN117777501A

  • Complex, method of producing the complex, rubber composition, and pneumatic tire

    JP2012236878A

  • A process to prepare high-quality natural rubber-silica masterbatch by liquid phase mixing

    WO2016014037A1